Jurisdiction and Due Process Challenges in Addressing Cross-Border Cybercrime - AllahRakha, Naeem (Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2024)
Cross-border cybercrime is identified as a growing concern due to the inherently borderless nature of cyberspace and the legal complexities associated with international cooperation and collaboration. Therefore, this research aims to examine the effectiveness of existing international legal frameworks, particularly the Budapest Convention on Cybercrime, in harmonising national legislation and supporting cross-border investigations. A doctrinal research methodology was adopted to review current cybercrime regulations and assess how international standards related to due process and prosecution contribute to safeguarding individual rights and ensuring fair trials in cross-border contexts. However, the current legal frameworks for collecting and sharing digital evidence across jurisdictions remain fragmented, posing substantial challenges to practical cooperation among nations. This fragmentation was further exacerbated by the rapid advancement of digital technologies, which continued to outpace legal reform. Law enforcement agencies now face growing legal and privacy-related challenges, particularly when attempting to access cross-border data stored on cloud-based platforms. Moreover, the execution of mutual legal assistance requests in cybercrime investigations continued to remain slow and inefficient, largely due to procedural bottlenecks and a lack of coordination. Significant gaps within existing international frameworks continue to hinder lawful access to electronic evidence. Additionally, investigations are frequently delayed due to language differences, conflicting legal systems, and inadequate technical capacity among national authorities. These persistent challenges underscore the urgent need for a coordinated and standardised global strategy to address cross-border cybercrime.